Evaluation of platelet GPIIb rs5911 polymorphism in relation to inflammation in patients with chronic obstructive pulmonary disease - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2015)
Chronic obstructive pulmonary disease (COPD) has susceptibility to inflammation, and hence demands investigation for/on its association with systemic inflammatory cytokines. Here, we evaluated platelet GPIIb rs5911 polymorphism and its relevance to inflammation in COPD patients using biomarkers. The study enrolled COPD patients (n=40) from S B Sureyyapasa Thoracic Disease Research & Training Hospital during May 2009 to December 2011 and healthy volunteers (n=24) from the Faculty of Pharmacy Laboratories, Marmara University, Istanbul, Turkey. Patient demographics, smoking habits, duration of COPD, co-morbidities, hemogram, C-reactive protein, biochemical and spirometry data were collected. Biomarker's levels were quantitated by ELISA. After DNA isolation, GPIIb/Ilia and GPUb polymorphisms were determined by PCR-RFLP, and gel electrophoresis to determine ITGA2B rs5911 polymorphism. Mean age was: patients=60.3 +/- 11.8 years and controls=51.4 +/- 7.0 years. There was significant difference in patient's disease periods (acute 9.8 +/- 6.9 vs. stable 1.6 +/- 1.1 years, P <0.05). 70% COPD patients had co-morbidities. Patients vs. control levels were: IL-6 (148.4 +/- 18.4 vs. 139.6 +/- 16.3 pg/mL; P =0.60), IL-10 (119.5 +/- 30.2 vs. 106.5 +/- 13.9 pg/mL; P =0.44), TNF-a (483.8 63.7 vs. 447.3 +/- 46.3 pg/mL; P =0.018). IL-6 and IL-10 levels were found decreased while hemoglobin, hematocrit, leukocyte, platelet count increased. Similarly, TNF-a also decreased while hematocrit and leukocyte increased (as the platelet counts also increased). Patient's genotypes were 41.5% T/T (homolog-normal), 38.9% T/G (heterolog-polymorphic), 19.4% G/G (homolog-polymorphic), and control's 33.3% T/T, 60% T/G, 6.7% G/G. While the T/T genotype patients were younger with longer COPD duration, G/G genotype cases were older, less smoker, and less hypertensive. The G/G genotype cases had more IL-10 vs. T/T cases. G/G genotype patients were older compared to others. Over all, the systemic inflammatory cytokine levels were relatively higher in COPD patients suggesting inflammatory response. Despite less smoking, G/G homolog polymorphism showed susceptibility to inflammation.
Keywords: Biomarkers; Cigarette smoking; COPD; Gene Polymorphism; Glycoprotein IIb; Platelets